Influence of Work Facilities and Abilities Village Officials Communication Against Quality of Public Services in Dengeng-Dengeng Village Pitu Riase District, Sidrap Regency - Arni; Edi Jusriadi; Andi Risfan Risaldi (Agency Journal of Management and Business, 2024)
This research aims to determine and analyze the influence of work facilities and communication abilities of village officials on the quality of public services in Dengeng-Dengeng Village, Pitu Riase District, Sidrap Regency. The sample data collection technique uses the Slovin formula. The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. Data collection techniques were carried out using questionnaires, observation and documentation. In this research, the data sources used in data collection include primary data and secondary data. The data analysis technique used is statistical calculations using the Statistical for the Social Science (SPSS) application version 25. This can be seen from the results of SPSS data processing where the sig value is 0.001<0.05 and has a value of t_(hitung )0.9071> t_tabel0. ,2028. The Communication Ability variable (X2) also has a positive and significant effect on the quality of public services (Y), which can be seen from the significant value of 0.000<0.05. and the value t_(hitung )0.6054> t_tabel0.2028.